2004
DOI: 10.1002/chem.200400187
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide(III) Complexes of DOTA–Glycoconjugates: A Potential New Class of Lectin‐Mediated Medical Imaging Agents

Abstract: The in vitro relaxivity of the Gd III -glycoconjugates was studied by 1 H nuclear magnetic relaxation dispersion (NMRD), yielding parameters close to those reported for other DOTA monoamides.The known recognition of sugars by lectins makes these glycoconjugates good candidates for medical imaging agents (MRI and gamma scintigraphy).3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
47
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 55 publications
1
47
1
Order By: Relevance
“…Although these are often highly convenient and flexible, they also have disadvantages, such as the toxicity (22) of CdS-based fluorescent quantum dots and the ligand-lability of gold clusters (23,24), which is exacerbated in biological media (25). The use of glycosylated contrast agents, until now, has been limited to T 1 -type reagents that rely on water exchange in their inner coordination sphere (26)(27)(28)(29)(30). They bring with them disadvantages of low sensitivity and low avidity for carbohydrate-binding protein targets since they display low carbohydrate copy numbers (31).…”
mentioning
confidence: 99%
“…Although these are often highly convenient and flexible, they also have disadvantages, such as the toxicity (22) of CdS-based fluorescent quantum dots and the ligand-lability of gold clusters (23,24), which is exacerbated in biological media (25). The use of glycosylated contrast agents, until now, has been limited to T 1 -type reagents that rely on water exchange in their inner coordination sphere (26)(27)(28)(29)(30). They bring with them disadvantages of low sensitivity and low avidity for carbohydrate-binding protein targets since they display low carbohydrate copy numbers (31).…”
mentioning
confidence: 99%
“…Chemically well-defined, mono disperse and characterized multivalent agents can be assembled by an alternative molecular design: the conjugation of dendrimeric-clustered carbohydrate bifunctional reagents through spacers to an MRI reporter group. Various Gd(III) complexes of the DTPA-and DOTA-type ligands, peripherally substituted with one or more targeting group(s) consisting of a clustered carbohydrate of variable valence, with different topologies (FiguRe 3), containing an increasing number of terminal galactosyl (Gal), lactosyl (Lac) or glycosyl (Glc) groups, have been synthesized and studied [31][32][33][34][35][36]. The ligands included various DOTA monoamide derivatives (FiguRe 4), with one (DOTAGal, DOTAGlc and DOTALac; 9), two (DOTAGal 2 , DOTAGlc 2 and DOTALac 2 ;10) or four (DOTAGal 4 ; 12) terminal sugar groups, one DOTA cis-bisamide derivative with two terminal sugar groups (DO2A(cis)Gal 2 ; 11) and DTPA bisamides with two (DTPAGal 2 and DTPALac 2 ; 13) or four (DTPAGal 4 ; 14) terminal sugar groups.…”
Section: Mri Contrast Agentsmentioning
confidence: 99%
“…The ligands included various DOTA monoamide derivatives (FiguRe 4), with one (DOTAGal, DOTAGlc and DOTALac; 9), two (DOTAGal 2 , DOTAGlc 2 and DOTALac 2 ;10) or four (DOTAGal 4 ; 12) terminal sugar groups, one DOTA cis-bisamide derivative with two terminal sugar groups (DO2A(cis)Gal 2 ; 11) and DTPA bisamides with two (DTPAGal 2 and DTPALac 2 ; 13) or four (DTPAGal 4 ; 14) terminal sugar groups. All dendrimeric sugar units were bound thioglycosidically, in order to prevent them from being cleaved off by enzymes [32][33][34][35]. The 1 H nuclear magnetic relaxation dispersion (NMRD) profiles showed that the relaxivity increase of these compounds relative to the respective parent compounds without the sugar derivatives (Gd-DOTA; 2 and Gd-DTPA-BMA; 3) is much lower that that expected for their molecular weight increase [32,33].…”
Section: Mri Contrast Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] We synthesized a DOTA derivative (2) functionalized with a pendant primary amine by following literature procedures. [11] The DOTA ligand was condensed with the activated NHS ester groups along the polymer backbone. Under the reaction conditions, the terminal dithioester derivative was cleaved to the primary thiol, as shown in Scheme 1.…”
mentioning
confidence: 99%